Hubungan Antara Terpaan Informasi Kelompok Rujukan Online Dan Kelompok Rujukan Offline Dengan Keputusan Pembelian Kamera Sony A7ii - Binarso Budiono Budiono; Tandiyo Pradekso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Cameras have become a necessity for social media users to upload interesting content. There are several brands on the camera market today, such as Lumix, Olympus, Fujifilm, Sony, Canon, Nikon. Because the camera is a product with high involvement that makes consumers have to be involved and conduct a search before making a purchase decision, from the many brands that circulate consumers get and search for information through the reference group that they use to make decisions about which camera to buy. The exposure of information obtained by consumers comes from online referral groups and offline referral groups. Thus this study aims to determine the relationship between exposure to information from online referral groups and offline reference groups with the decision to purchase Sony A7II cameras. The theory used in this research is the Theory Reference Group and Information Integration Theory. This research is a quantitative research with explanatory type. This study uses a non-random technique with a total sample of 60 people aged 18-30 years on the island of Java. The results of the Kendall Tau correlation analysis show that exposure to online referral group information has a strong relationship with the purchase decision of Sony A7II camera, indicated by a coefficient value of 0.563 and significance of 0.000, and the relationship between exposure to offline referral group information with purchasing decisions of Sony A7II cameras also has this strong relationship can be seen from the test results, the correlation coefficient value is 0.503 and the significance value is 0.000. from the results obtained it is recommended for Sony camera brands, to be able to hold offline seminars that invite photographic figures and there are Sony camera product displays, so that consumers can immediately feel the performance of the camera so that consumers can make purchases after getting information.